Digital technologies in the context of continuing education for university professors (Research, Society and Development, 2022)
This essay articulates contemporary issues about the continued formation of university professors using digital technologies. According to the literature, it's essential that reflections conjecture the complex context of diversity and unpredictability, which causes challenges that are sometimes insurmountable both to training and to pedagogical practice. In this scenario, we question the meanings of digital technologies in teacher education. The objective is to analyze, using Bakntin lens, the narratives produced in recent years about digital technologies in the context of the continuing education of university professors. It is a theoretical discussion that seeks to answer the proposed question using the bibliographic research method. The results indicate that both teacher education and digital technologies are built through hybrid statements, whose constructions are composed by fusion of different ideas, perceptions and categorizations, always susceptible to new narratives.